Adição de Michael de α,α-Diciano-Olefinas a Chalconas via organocatálise assimétrica empregando solvente derivado de biomassa - Martelli, Lorena Suelen Ribeiro (2018)
In recent years, organocatalysed reactions have become an important field in asymmetric synthesis. Particularly, Michael addition reactions using various donors and acceptors have been explored to generate substrates that can be used as building blocks in other transformations. Chalcones, for example, are widely used as Michael acceptors not only because of their privileged reactivity but also due to their biological activities already reported. On the other hand, the α,α-dicyanoolefins proved to be a very versatile reagent, capable of acting as Michael acceptors as well as vinylogous nucleophiles in organocatalysed reactions. However, to date, the addition of α,α-dicyanoolefins to chalcones has not yet been explored. Considering the potential biological activity of the products, in this study, we report the use of a bifunctional catalyst derived from the alkaloid cinchona to perform the enantioselective addition of α,α-dicyanoolefins to chalcones. Based on preliminary results obtained in our research group, the Michael addition reaction was optimized by investigating time, acid additive, temperature, catalyst loading and solvent. Looking for more environmentally sustainable conditions, we have tested a series of greener solvents and the bio-derivative 2-MeTHF at 15 mol% of catalyst proved to be the best for this transformation. Having established the best reaction condition for this reaction, we investigated the scope and limitations of the developed protocol, where 17 new compounds were synthesized with yields in the range of 28-66% and 71-98% enantiomeric excesses. With the goal to increase the structural diversity, attempts to cyclize the Michael adducts were performed using different bases and acids.